Brain fingerprint and subjective mood state across the menstrual cycle - Cipriano, Lorenzo; Liparoti, Marianna; Troisi Lopez, Emahnuel; Romano, Antonella; Sarno, Laura; Mazzara, Camille; Alivernini, Fabio; Lucidi, Fabio; Sorrentino, Giuseppe; Sorrentino, Pierpaolo (Frontiers in Neuroscience, 2024)
BackgroundBrain connectome fingerprinting represents a recent and valid approach in assessing individual identifiability on the basis of the subject-specific brain functional connectome. Although this methodology has been tested and validated in several neurological diseases, its performance, reliability and reproducibility in healthy individuals has been poorly investigated. In particular, the impact of the changes in brain connectivity, induced by the different phases of the menstrual cycle (MC), on the reliability of this approach remains unexplored. Furthermore, although the modifications of the psychological condition of women during the MC are widely documented, the possible link with the changes of brain connectivity has been poorly investigated.MethodsWe conducted the Clinical Connectome Fingerprint (CCF) analysis on source-reconstructed magnetoencephalography signals in a cohort of 24 women across the MC.ResultsAll the parameters of identifiability did not differ according to the MC phases. The peri-ovulatory and mid-luteal phases showed a less stable, more variable over time, brain connectome compared to the early follicular phase. This difference in brain connectome stability in the alpha band significantly predicted the self-esteem level (p-value <0.01), mood (p-value <0.01) and five (environmental mastery, personal growth, positive relations with others, purpose in life, and self-acceptance) of the six dimensions of well-being (p-value <0.01, save autonomy).ConclusionThese results confirm the high reliability of the CCF as well as its independence from the MC phases. At the same time the study provides insights on changes of the brain connectome in the different phases of the MC and their possible role in affecting women’s subjective mood state across the MC. Finally, these changes in the alpha band share a predictive power on self-esteem, mood and well-being.